Project-based learning in improving scientific literacy: Systematic literature review - Hudha, Muhammad Nur; Fajriyah, Mujtahidatul Ilmi; Rosyidah, Firda Ulya Nur; Ayu, Hena Dian (Psychology, Evaluation, and Technology in Educational Research, 2023)
Scientific literacy is a necessary competency for students in the 21st century. The low level of scientific literacy among students in Indonesia can be attributed to a number of factors, including the learning model used. Several studies indicate that project-based learning can enhance students' scientific literacy. The objective of this study is to present the findings of a literature review on project-based learning for increasing scientific literacy. The method employed was a systematic literature review. This study collected data from 2012 to 2022 based on a prism-shaped data extraction procedure diagram with specific criteria. According to the findings of this study, the project-based learning model can enhance scientific literacy in multiple fields of science, including physics, chemistry, biology, science, epidemiology, and environmental projects. Project-based learning is consistent with interdisciplinary learning because it naturally incorporates a variety of academic skills, such as reading, writing, and calculation, which can directly contribute to the development of conceptual understanding through the incorporation of other disciplines. Thus, the use of PjBL can improve students' scientific literacy.